Pendampingan Kelompok Pengolah dan Pemasaran (Poklahsar) sebagai Alternatif Mata Pencaharian Penangkapan Hiu dan Pari - Daeng Nur Azizatul Magfiroh; Muhsin; M Said Ramdlan; Soraya Gigentika (UNITY: Journal of Community Service, 2026)
The high dependence of coastal communities in Tanjung Luar on the fisheries sector, including shark and ray fishing, has driven the development of sustainable alternative livelihoods. This community service program aimed to assist Processing and Marketing Groups (Poklahsar) in developing fish floss processing enterprises as a value-added product. The program was conducted on May 18 and 20, 2026, in Tanjung Luar, East Lombok, using a participatory approach that included initial surveys, group coordination, extension activities, fish floss production practices, and evaluation of the mentoring program. The results indicated an improvement in participants' knowledge and skills in processing, packaging, and marketing fish floss products. In addition to adding value to fishery products, the fish floss processing business has the potential to become an alternative source of income that can reduce the community's dependence on shark and ray fishing. Therefore, this Poklahsar mentoring program supports the economic empowerment of coastal communities while contributing to the sustainable conservation of marine resources.